Marketing Strategy as an Alternative to Increase the Competitiveness of Bina Insani University Graduates - Lala Wiladiyah; Tantri Yanuar Rahmat Syah; Suwarto; Rhian Indradewa (Syntax Idea)
Higher education has a high position in producing competitive graduates. Competitive competitors also need to have a marketing strategy for promoting their graduates so that they can be said to be competitive and quickly absorbed by various companies. This study aimed to analyze marketing strategies as an alternative to increasing the competitiveness of Bina Insani University graduates. The research method used is qualitative research. The data collection techniques used in this research are literature study and observation. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that marketing strategies as an alternative to increasing the competitiveness of Bina Insani University graduates were carried out in several ways, including market segmentation, targeting, positioning, and sales and revenue stream projections.